Determinants of Import Demand for Crude Oil in Pakistan - Asif, Muhammad Farhan; Ali, Shafaqat; Safdar, Hina (The journal of contemporary issues in business and government, 2020)
This study analyzes determinants of import demand for crude oil in Pakistan. For this purpose, Co- integration technique has been used to estimates long run relationship between crude oil import demand and its determinants; GDP per capita, price of crude oil, real effective exchange rate, and electricity production from oil sources. This import demand of crude oil function empirically tested for Pakistan. Results show that import demand elasticity of crude oil with respect to its different determinants is different. The import demand of crude oil is affected positively and significantly by GDP per capita and electricity production from oil sources. Price and real effective exchange rate have negative and significant impact on crude oil import demand in Pakistan. This study provides guidelines for macroeconomic policymakers in order to formulate comprehensive and appropriate import policy for crude oil.